GINES, Kathryn T. Sartre, Beauvoir, and the Race/Gender Analogy: A Case for Black Feminist Philosophy. - Rivera Berruz, Stephanie (Sapere Aude, 2013)
Review of GINES, Kathryn T. Sartre, Beauvoir, and the Race/Gender Analogy: A Case for Black Feminist Philosophy. In DAVIDSON, Maria del Guadalupe; GINES, Kathryn T.; MARCANO, Donna-Dale L. (orgs.). Convergences: Black Feminism and Continental Philosophy.